Economic optimisation for an imperfect production system with rework and scrap rate. (7th July 2010) - Chen, Jen-Ming; Lin, Ya-Hui; Chen, Yan-Chun
This paper developed an integrated model in considering the situations of an imperfect process with imperfect maintenance and shortage, and an imperfect rework process for the determination of economic production quantity. This imperfect process has a general deterioration distribution with increasing hazard rate. Even with periodic preventive maintenance, such a production system cannot be recovered as good as new. As the process produces non-conforming items, a percentage of them are scrapped and the others are reworked. There is a percentage of the reworking items fail the repairing and become scrap items in the imperfect rework process. We use numerical analyses to simulate the effect of changes in the various parameters on the optimal solution. And look at the optimal inspection interval, inspection frequency and production quantity that maximum total profit which the advantages of rework process were explored.